Decrease in Behavioral Problems and Trauma Symptoms Among At-Risk Adopted Children Following Web-Based Trauma-Informed Parent Training Intervention. Issue 2 (3rd March 2016) - Razuri, Erin Becker; Hiles Howard, Amanda R.; Parris, Sheri R.; Call, Casey D.; DeLuna, Jamie Hurst; Hall, Jordan S.; Purvis, Karyn B.; Cross, David R.
Abstract : Children who have experienced early adversities are at risk for behavioral problems and trauma symptoms. Using a two-group, pre–post intervention design, the authors evaluated the effectiveness of an online parent training for Trust-Based Relational Intervention, a trauma-informed, attachment-based intervention, in reducing behavioral problems and trauma symptoms in at-risk adopted children. Children of parents in the treatment group ( n  = 48) demonstrated significant decreases in behavioral problems and trauma symptoms after intervention. Scores for children in a matched-sample control group did not change. Findings suggest this intervention can effectively reduce behavioral problems and trauma symptoms in children with histories of adversities.